Effect of Sappanwood Extract (Biancaea sappan (L.) Tod.) on the Elimination Phase of the Pharmacokinetic Profile of Glibenclamide in Wistar Rats (Rattus norvegicus) - Vidiani, Anak Agung Pradnya Paramitha; Tapun, Margareta Chintami; Sa’adah, Anifatus; Adrianto, Madyo (MPI (Media Pharmaceutica Indonesiana), 2025)
Type 2 diabetes mellitus is characterized by chronic hyperglycemia, and glibenclamide remains a commonly used oral antidiabetic. Concomitant consumption of sappanwood extract (Biancaea sappan (L.) Tod.) is widespread in Indonesia, raising concerns about herb–drug interactions. This study investigated whether sappanwood modifies the elimination of glibenclamide in Wistar rats. Rats were randomized into three groups: Group I received glibenclamide 10 mg/kg BW; Group II received sappanwood extract 400 mg/kg BW; Group III received the combination. Blood was collected from the retro‐orbital plexus at 20, 22, and 24 h and analyzed by UV–Vis spectrophotometry. Pharmacokinetic parameters were derived by linear regression and residual analysis. In Group I, the terminal log‐linear profile yielded an elimination rate constant (Ke) of 0.1218 h−1 and an elimination half‐life (t1⁄2) of 5.79 h. In Group III, co‐administration with sappanwood produced Ke = 0.0066 h−1 and t1⁄2 = 105 h, indicating a pronounced slowing of glibenclamide elimination relative to control. Group II did not receive glibenclamide and was excluded from pharmacokinetic calculations. Sappanwood extract markedly altered glibenclamide disposition, consistent with a pharmacokinetic herb–drug interaction. The findings suggest that bioactive flavonoids (e.g., Brazilin and quercetin derivatives) may inhibit metabolic pathways relevant to glibenclamide clearance, leading to prolonged exposure.